GE_GERICHTE P/14524/2018 vom 7. Dezember 2018 - GE Cour de justice (2018)
ORGANISATION(PROCÉDURE) ; COMPÉTENCE FONCTIONNELLE ; DÉTENTION(INCARCÉRATION) ; TRAITEMENT HOSPITALIER ; ÉTABLISSEMENT HOSPITALIER | CPP.234; LaCP.28; RCurabilis.18; RCurabilis.21; LEPM.16